Imagining Head Smashed In: Aboriginal Buffalo Hunting on the Northern Plains - Jack W. Brink (Athabasca University Press, 2008)
At the place known as Head-Smashed-In in southwestern Alberta, Aboriginal people practiced a form of group hunting for nearly 6,000 years before European contact. The large communal bison traps of the Plains were the single greatest food-getting method ever developed in human history. Hunters, working with their knowledge of the land and of buffalo behaviour, drove their quarry over a cliff and into wooden corrals. The rest of the group butchered the kill in the camp below. Author Jack Brink, who devoted 25 years of his career to "The Jump," has chronicled the cunning, danger, and triumph in the mass buffalo hunts and the culture they supported. He also recounts the excavation of the site and the development of the Head-Smashed-In Buffalo Jump Interpretive Centre, which has hosted 2 million visitors since it opened in 1987. Brink's masterful blend of scholarship and public appeal is rare in any discipline, but especially in North American pre-contact archaeology. Brink attests, "I love the story that lies behind the jump-the events and planning that went into making the whole event work. I continue to learn more about the complex interaction between people, bison and the environment, and I continue to be impressed with how the ancient hunters pulled off these astonishing kills."